Pengaruh Dana Perimbangan Terhadap Pertumbuhan Ekonomi Di Provinsi Kepulauan Bangka Belitung Tahun 2010-2018 - Yulizar Bachtiar (Ekopem: Jurnal Ekonomi Pembangunan, 2021)
Equal economic growth, one of which uses funds sourced from APBN revenues that are allocated to the regions (autonomous) to fund regional needs in the context of the implementation of Decentralization or called the Balancing Fund. In Law Number 32 Year 2004 it is explained that the balance of central and regional finances is intended to support funding of affairs to the Regional Government. The purpose of this study was to determine the effect of the Balancing Fund on Economic Growth in the Bangka Belitung Islands Province. The data used in this study are secondary data during the period 2010-2018. Analysis of the data used using simple linear regression analysis conducted through several stages, including through the classical assumption test using the Kolmogorov Smirnov test, the Spearman Rank test, and the Durbin-Watson test. Research Results Show that the Balancing Fund has a positive effect on Economic Growth in the Bangka Belitung Islands Province in 2010-2018. This means that if the Balance Fund increases, the Economic Growth in the Bangka Belitung Islands Province will increase. Vice versa if the Balancing Fund decreases then Economic Growth in the Bangka Belitung Islands Province will decrease.